2019
DOI: 10.1108/scm-09-2018-0318
|View full text |Cite
|
Sign up to set email alerts
|

Ambidextrous supply chain managers in a slow clockspeed industry: evidence from a Brazilian adhesive manufacturer

Abstract: Purpose Conventional wisdom posits that firms in slow clockspeed industries usually favor exploitation over exploration, prioritizing the need to increase efficiency, reduce costs and invest in process improvements. However, what happens when such firms face structural changes in the long run? The authors claim that even firms in slow clockspeed industries should be ambidextrous, that is, they should develop both exploration and exploitation capabilities. Supply chain (SC) managers are key players in enabling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“… Aslam et al (2018) ; Eckstein et al (2015) ; Wamba et al (2020) ; Aslam et al (2020) ; Shukor et al (2020) ; Alzoubi & Yanamandra (2020) ; Suresh et al (2020) ; Aslam et al (2018) ; Shqairat & Sundarakani (2018) ; Tuan (2016) ; Liu et al (2015b) . I9 Supply chain ambidexterity SC ambidexterity refers to a manufacturer's efforts to refine/extend its existing resources and to develop new supply chain competencies and yield performance benefits, especially for large manufacturing firms Partanen et al (2020) ; Partanen et al (2020) ; Aslam et al (2020) ; Ojha et al (2018) ; Lee & Rha (2016) ; Princes (2020) ; Pu et al (2018) ; Burin et al (2020) ; Souza-Luz & (2019) ; Güemes-Castorena & Ruiz-Monroy (2020) ; Makhashen et al (2020) ; Shams et al (2020) ; Yalcin et al (2019) ; Goh & Eldridge (2019) ; Im et al (2019) ; Qamar et al (2019) . I10 Supply chain collaboration SC collaboration is a model in which members of the supply chain share risks and resources in order to improve the competitive advantage of the entire supply chain.…”
Section: Resultsmentioning
confidence: 99%
“… Aslam et al (2018) ; Eckstein et al (2015) ; Wamba et al (2020) ; Aslam et al (2020) ; Shukor et al (2020) ; Alzoubi & Yanamandra (2020) ; Suresh et al (2020) ; Aslam et al (2018) ; Shqairat & Sundarakani (2018) ; Tuan (2016) ; Liu et al (2015b) . I9 Supply chain ambidexterity SC ambidexterity refers to a manufacturer's efforts to refine/extend its existing resources and to develop new supply chain competencies and yield performance benefits, especially for large manufacturing firms Partanen et al (2020) ; Partanen et al (2020) ; Aslam et al (2020) ; Ojha et al (2018) ; Lee & Rha (2016) ; Princes (2020) ; Pu et al (2018) ; Burin et al (2020) ; Souza-Luz & (2019) ; Güemes-Castorena & Ruiz-Monroy (2020) ; Makhashen et al (2020) ; Shams et al (2020) ; Yalcin et al (2019) ; Goh & Eldridge (2019) ; Im et al (2019) ; Qamar et al (2019) . I10 Supply chain collaboration SC collaboration is a model in which members of the supply chain share risks and resources in order to improve the competitive advantage of the entire supply chain.…”
Section: Resultsmentioning
confidence: 99%
“…Probst et al (2011) emphasize that becoming an ambidextrous organization is first and foremost a leadership challenge, and business leaders need to balance current and new activities, combining short-term and long-term thinking, and craft emotionally engaging visions while staying focused on execution. In the specific area of supply chain, Souza-Luz and Gavronski (2020) found that the characteristics of an ambidextrous supply chain manager are a holistic yet focused approach, prior experience in multiple functional areas, technical knowledge, network connectivity, openness for sharing ideas with other managers, empathy skills and entrepreneurial capabilities. From a theoretical point of view, Bledow et al (2009) proposed that ambidextrous leaders are characterized by cognitive as well as behavioral complexity and are able to dynamically adapt their tactics (such as being directive or providing autonomy) to contextual demands.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying argument is that growing supply chain complexities require managers to possess ambidexterity using which they are expected to execute two critical activitiesfor instance, exploration of opportunities on the one hand while simultaneously exploiting the resources to benefit their firms on the other (Aslam et al, 2018;O'Reilly lll and Tushman, 2011). Following the extant literature, we argue that it is necessary to study the application of such managerial ambidexterity due to (1) managerial ambidexterity being considered as a key antecedent to organisational ambidexterity (Raisch and Birkinshaw, 2008;Souza-Luz and Gavronski, 2020) and OM scholars specifically arguing for managerial ambidexterity to be suitable to manage complex supply chain challenges (Aslam et al, 2018;Ojha et al, 2018), ( 2) coopetition being an ambidextrous form of relationship is argued to benefit firms when managerial ambidexterity is employed (Lundgren-Henriksson and Kock, 2016;Seepana et al, 2020) and ( 3) coopetition literature consistently draws parallels between exploration and exploration aspects of ambidexterity and the cooperation and competition aspects of coopetition (Seepana et al, 2020;Makhashen et al, 2020) and suggests that managers' pursuit of simultaneous exploration and exploitation activities is likely to play a crucial role in resource configuration in order to manage the coopetitive activities of their respective firms (Seepana et al, 2020). Despite this growing theoretical support, the practice of how managerial ambidexterity could transform resources into a competitive advantage within ambidextrous relationships is yet to be uncovered.…”
Section: Significance Of Managerial Ambidexteritymentioning
confidence: 98%
“…Secondly, there is little focus on quantitatively examining the ability of managerial ambidexterity (Raisch and Birkinshaw, 2008), particularly within ambidextrous relationships (Turner et al, 2018;Blome et al, 2013;Souza-Luz and Gavronski, 2020), in influencing the firm's resources for superior performance benefits. OM scholars, in particular, seek to understand the importance of managers in the development of ambidextrous forms of organisations including their supply chains to bring success to firms (Blome et al, 2013;Turner et al, 2018).…”
Section: Ijopm 4212mentioning
confidence: 99%
See 1 more Smart Citation